Vegetative propagation of Phytolacca acinosa Roxb. by rhizome cuttings: a step towards conservation and cultivation approach - Magray, Junaid A.; Wani, Bilal A.; Javid, Hanan; Islam, Tajamul; Ganie, Aijaz H.; Qadir, Roof Ul; Nawchoo, Irshad A. (Frontiers in Conservation Science, 2024)
Phytolacca acinosa Roxb. is a highly valuable multipurpose herb native to the Himalayan region. Unsustainable harvesting of this species due to its diverse uses has resulted in a rapid decline in its population across natural habitats, thereby necessitating its propagation and conservation. To overcome this challenge, the potential of P. acinosa rhizomes for ex situ regeneration was evaluated. The current study aims to develop a standard propagation protocol for P. acinosa. Rhizome cuttings derived by splitting whole rhizomes were used to study the effect of various hormones and soil compositions on their sprouting and growth performance. Soil compositions SC10 and SC5 consisting of soil, sand, pebbles, and vermicompost (1:1:1:1) and soil, sand, and vermicompost (1:1:1), respectively, were the most suitable compositions for the optimum growth of this species. The rhizome segments treated with GA3 (150ppm) induced the highest sprouting percentage (91.67%), with a minimum sprouting time of 23.25 days. The maximum root length (9.25 cm), shoot length (16.5 cm), and leaf number (11.25) were recorded for GA3 (150ppm) treated rhizome cuttings. Overall, the results of the present study helped in establishing a cost-effective, rapid, efficient, and simple mass propagation method for the target species. The results of this study will serve as a guide for the large-scale cultivation, effective conservation, and sustainable utilization of this economically valuable medicinal herb.